VOLUME MEASUREMENTS OF NORMAL BONY ORBIT AND ORBITAL SOFT TISSUE IN CHILDREN BY COMPUTED TOMOGRAPHIC ANALYSIS - O. Yu. Yatsenko; E. A. Koroleva; I. A. Mel’nikov (Вестник рентгенологии и радиологии, 2017)
Objective: to study the volumetric data of the bone of the orbit and its soft tissues in children is normal.Material and methods. A research into CT scans of 50 children (80 orbits) without orbital abnormality was conducted. The computed tomography imaging was performed routinely, with both axial and frontal sections obtained. Section thickness measured 1.0 mm at intervals of 1.00 mm.Results. The article presents volume measurements for normal bony orbits and orbital soft tissue (extraocular muscle, retrobulbar tissue, optic nerve, and lacrimal gland) in children in vivo, with regard to age peculiarities. The orbital tissue volume ratios presented in the article allow for conclusions about age-specific changes in the anatomy and topography of the orbit in children.Conclusion. The growth of a child is accompanied by a continuous steady increase in the bony orbit and orbital soft tissue volume, which reaches 21.93 cm3 and 14.87 cm3 respectively by the age of 15 to 16 years. With age, the volume of orbital soft tissues shows a greater increase than the volume of the bony orbit, which leads to a change in topographic ratio of orbital tissues (the muscle “cone” widens, the eyeball protrudes forward).